A literature review of mobility services: definitions, modelling state-of-the-art, and key considerations for a conceptual modelling framework. Issue 3 (3rd May 2020) - Calderón, Francisco; Miller, Eric J.
ABSTRACT: This paper presents a comprehensive literature review focused on the supply side of mobility services, providing relevant insights at the conceptual, operational, and modelling levels. Definitions are first drawn from the Mobility as a Service paradigm due to its predominance in the literature. This is followed by an assessment of the operational features of a range of mobility services, including carsharing, bikesharing, ridehailing, and demand responsive transit. To conclude the review, the state-of-the-art in modelling approaches for mobility services is reported, at different levels of complexity and integration. Three of the most important findings and arguments from this paper suggest that a high degree of generality exists for operational features of mobility services; that it is essential to make a distinction between Mobility as a Service and a mobility service in isolation; along with the argument that human agency should be carefully considered in modelling efforts, both for user agent and driver agent decision-making processes. Finally, key considerations are proposed for the future development of a conceptual framework for modelling the supply side of mobility services, which would have a generic service provider model as its core component.